Resource allocation for biomedical research: analysis of investments by major funders - Ambinintsoa H. Ralaidovy; Taghreed Adam; Philippe Boucher (BMC, 2020)
Abstract Background Data on grants for biomedical research by 10 major funders of health research were collected from the World RePORT platform to explore what is being funded, by whom and where. This analysis is part of the World Health Organization Global Observatory on Health Research and Development's work with the overall aim to enable evidence-informed deliberations and decisions on new investments in health research and development. The analysis expands on the interactive data visualisations of these data on the Observatory's website and describes the methods used to enable the categorisation of grants by health categories using automated data-mining techniques. Methods Grants data were extracted from the World RePORT platform for 2016, the most recent year with data from all funders. A data-mining algorithm was developed in Java to categorise grants by health category. The analysis explored the distribution of grants by funder, recipient country and organisation, type of grant, health category, average grant duration, and the nature of collaborations between recipients of direct grants and the institutions they collaborated with. Results Out of a total of 69,420 grants in 2016, the United States of America's National Institutes of Health funded the greatest number of grants (52,928; 76%) and had the longest average grant duration (6 years and 10 months). Grants for research constituted 70.4% (48,879) of all types of grants, followed by grants for training (13,008; 18.7%) and meetings (2907; 4.2%). Of grant recipients by income group, low-income countries received only 0.2% (165) of all grants. Almost three-quarters of all grants were for non-communicable diseases (72%; 40,035), followed by communicable, maternal, perinatal and nutritional conditions (20%; 11,123), and injuries (6%; 3056). Only 1.1% of grants were for neglected tropical diseases and 0.4% for priority diseases on the WHO list of highly infectious (R&D blueprint) pathogens. Conclusions The findings highlight the importance of considering funding decisions by other actors in future health research and capacity-strengthening decisions. This will not only improve efficiency and equity in allocating scarce resources but will also allow informed investment decisions that aim to support research on public health needs and neglected areas.